Multimodality in the teaching of critical thinking skills / Syakirah Mohammed...[et al.] - Mohammed, Syakirah; Ahmad @ Ahmad Jali, Fathiyah; Amat, Rafidah (2019)
Critical thinking skills are one of the most important skills to be possessed by an individual in surviving this world of globalization. Due to this, the teaching of these skills is given paramount importance in higher institutions of learning the world over. The teaching of these skills is found embedded in many areas including in the Teaching of English as a Second and Foreign Language. However, Critical thinking skills is found to be not an easy skill to teach. Traditional method employed in the teaching of the skills often prove inefficient especially in ensuring the transfer across domain. This paper explores the possibility of using multimodality both as material and methodology in the teaching of critical reading and thinking skills. Multimodality that allows meaning making from different semiotic modes may allow greater engagement by the learners; thus allowing them to better retain the concepts that they have learned and subsequently transfer this knowledge across their learning domain